On the irrelevance of the leverage effect - Peter Nippel (Universität Kiel, Institut für Betriebswirtschaftslehre, 2001)
Financial leverage increases the expected return on equity. We show that this leverage effect is not only irrelevant for shareholders' present wealth but also for the return on their investments. This result is straightforward if we do not only look at the return on equity but at the return on shareholders' total wealth. Any relevance leverage may have is definitely due to market imperfections. These may simply cause differences in market access for firms and individuals or lead to agency problems between investors and management.
Keywords: G32; 650; Leverage; shareholder value; shareholders' return